A case of mediastinal teratoma with malignant transformation into angiosarcoma and relapse with multiple bone metastases that was cured by a multidisciplinary treatment. Issue 2 (11th November 2022) - Tani, Masaru; Nagahara, Akira; Takada, Shingo; Fujita, Kazutoshi; Fukuhara, Shinichiro; Uemura, Motohide; Kiuchi, Hiroshi; Imamura, Ryoichi; Nonomura, Norio
Abstract : Introduction: Complete resection is essential for the treatment of teratoma with malignant transformation, and if metastasis occurs, it will be difficult to cure. We report a case of primary mediastinal teratoma with differentiation into angiosarcoma that caused bone metastases but was cured by multidisciplinary treatment. Case presentation: A 31‐year‐old man with a primary mediastinal germ cell tumor underwent primary chemotherapy followed by post‐chemotherapy resection, with angiosarcoma due to malignant transformation found in the surgical specimen. Femoral diaphyseal metastasis was manifested, and he underwent femur curettage followed by radiation therapy of 60 Gy in parallel with 4 cycles of chemotherapy combining gemcitabine and docetaxel. Although thoracic vertebral bone metastasis emerged 5 months after treatment, intensity‐modulated radiation therapy was successful, and metastatic lesions have remained shrunken for 39 months after treatment. Conclusion: Even if complete resection is difficult, teratoma with malignant transformation may be cured by multidisciplinary treatment based on histopathology.